Manual Para Implantação De Um Ambulatório De Cosmiatria Para Os Serviços Credenciados De Formação Em Cirurgia Plástica - Santos, Leandro Menezes Lopes Dos [UNIFESP] (2018)
Introduction: Cosmiatry is an area of medicine that aims to expand and extend procedures for maintaining the beauty and appearance of the skin and its appendix. In the majority of accredited training services in Plastic Surgery by the Brazilian Society of Plastic Surgery (SBCP) there are no specific outpatient clinics for attendance and training in Cosmiatry. Objective: To develop a Manual for the implantation of an Ambulatory of Cosmiatry for Accredited Training Services in Plastic Surgery in Brazil. Method: A review of the literature was made on the bases Scielo, Pubmed, Lilacs, selected articles on Cosmiatry. Researched as norms of the National Agency of Sanitary Surveillance (ANVISA) and of the Brazilian Association of Technical Norms (ABNT) for the implantation of medical outpatient clinics. A manual has been created with this data. A questionnaire was applied for method validation using a statistical method - Delphi methodology, together with a group of specialists. Results: Creation of a manual with the selection of contents validated by 7 judges, plastic surgeons with expertise in Cosmiatry, for the implementation of an outpatient clinic for teaching and training in this area. The manual was published in printed and electronic form. Conclusion: A manual was developed for implantation of a Cosmiatry outpatient clinic for Accredited Training Services in Plastic Surgery in Brazil.